Green Infrastructure: analysis of the feasibility of Greenways in João Pessoa-PB - Brito, Maria Vitória Carneiro; Silveira, José Augusto Ribeiro da; Negrão, Ana Gomes; Pereira, Pedro Henrique dos Santos; Oliveira, Juliana Xavier Andrade de (Technical and Scientific Journal Green Cities, 2025)
Objective – Identify roads with potential for the implementation of Greenways in João Pessoa-PB and propose guidelines for urban readjustment.Methodology – Bibliographic, field and case study research, with the elaboration of environmental and urban thematic maps and application of evaluative criteria found in the literature.Originality/Relevance – The study is part of the gap on the methodological application of greenways in the context of Brazilian cities, contributing to the debate on sustainable urban planning.Results – Identification of five potential pathways, selection of three for in-depth diagnosis, and formulation of specific transformation guidelines.Theoretical/Methodological Contributions – Progress in the methodological delimitation of greenways in urban areas, integrating environmental and urban criteria.Social and Environmental Contributions – Potential for qualification of public open spaces, increased ecological connectivity, environmental comfort and promotion of active mobility.
Keywords: Green Infrastructure; Greenways; Urban Environmental Planning